Micro Data, Heterogeneity, and the Evaluation of Public Policy: Nobel Lecture - Heckman, James J. (Journal of Political Economy, 2001)
This paper summarizes the contributions of microeconometrics to economic knowledge. Four main themes are developed. (1) Microeconometricians developed new tools to respond to econometric problems raised by the analysis of the new sources of micro data produced after the Second World War. (2) Microeconometrics improved on aggregate time-series methods by building models that linked economic models for individuals to data on individual behavior. (3) An important empirical regularity detected by the field is the diversity and heterogeneity of behavior. This heterogeneity has profound consequences for economic theory and for econometric practice. (4) Microeconometrics has contributed substantially to the scientific evaluation of public policy.